2020
DOI: 10.21203/rs.3.rs-137775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Solution-Focused Counseling Therapy on Pregnancy Anxiety and Fear of Childbirth: A Randomized Clinical Trial

Abstract: Background & Aim: Fear of childbirth and pregnancy anxiety may affect the desire for normal delivery. No study has investigated the effectiveness of solution-focused counseling on either pregnancy anxiety or all factors comprising fear of childbirth. We aimed to investigate the effects of solution-focused counseling in reducing pregnancy anxiety and fear of childbirth.Methods and materials: This randomized clinical trial study was conducted on 121 nulliparous women in 2019. Participants with moderate to se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This result is similar to the results of the present study. Mortazavi and Mehrabadi (2021) found that solution‐focused counseling (five sessions) reduced pregnancy anxiety and fear of childbirth. Some studies show that preparation for childbirth through educational programs based on psychoeducation (Fenwick et al, 2018; Toohill, Fenwick, Gamble, Creedy, Buist, et al, 2014) and psychotherapy (Nieminen et al, 2016; Ucar & Golbasi, 2019) reduces fear of childbirth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is similar to the results of the present study. Mortazavi and Mehrabadi (2021) found that solution‐focused counseling (five sessions) reduced pregnancy anxiety and fear of childbirth. Some studies show that preparation for childbirth through educational programs based on psychoeducation (Fenwick et al, 2018; Toohill, Fenwick, Gamble, Creedy, Buist, et al, 2014) and psychotherapy (Nieminen et al, 2016; Ucar & Golbasi, 2019) reduces fear of childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducation aims for the individual to understand the problem, to identify oneself interventions in coping with the problem, and to actively participate in the solution process (Fenwick et al, 2018). Studies investigating the effect of solution‐focused psychoeducation (SFP) or counseling on fear of childbirth are limited (Mortazavi & Mehrabadi, 2021; Sharifzadeh et al, 2018). Sharifzadeh et al (2018) reported in their study that a six‐session solution‐focused midwifery counseling program is effective to reduce the fear of childbirth in women.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations